2020
DOI: 10.2174/1386207322666191203092715
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tolvaptan in the Treatment for Patients with Autosomal Dominant Polycystic Kidney Disease: A Meta-analysis

Abstract: Aim and Objective: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a common chronic kidney disease that leads to End-Stage Renal Disease (ESRD). The key target of this therapy is to prevent the progression of kidney failure. Tolvaptan could slow kidney cyst growth and are proven highly effective. The aims of this analysis are to perform a systematic review, estimate and evaluate the efficacy and safety of tolvaptan in ADPKD patients. Materials and Methods: Randomized controlled trials of tolvaptan in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the subgroup analysis, the effect of preserving kidney function was prominent in patients with more severe clinical phenotypes, similar to changes in TKV. Although there have been no reports considering ESKD as an outcome, the positive effect of preserving kidney function has been maintained in most studies [22,23]. Extrapolations from the results of the TEMPO 3:4 suggested that [24].…”
Section: Preserving Kidney Functionmentioning
confidence: 99%
“…In the subgroup analysis, the effect of preserving kidney function was prominent in patients with more severe clinical phenotypes, similar to changes in TKV. Although there have been no reports considering ESKD as an outcome, the positive effect of preserving kidney function has been maintained in most studies [22,23]. Extrapolations from the results of the TEMPO 3:4 suggested that [24].…”
Section: Preserving Kidney Functionmentioning
confidence: 99%
“…In addition, numerous extra-renal manifestations of the disease, such as pancreatic and liver cysts, increased blood pressure, and a higher risk of cerebral aneurisms have been reported [ 9 ]. As of today, the selective vasopressin V 2 receptor antagonist tolvaptan (Jinarc ® (EU, UK, Canada), Jynarque ® (USA), Samsca ® (Japan)) is the only available treatment that can slow cyst growth in ADPKD patients [ 10 , 11 ]. Through the inhibition of the binding of the antidiuretic hormone arginine vasopressin (AVP) to its receptor, tolvaptan diminishes cAMP production and thus cAMP-associated cyst cell proliferation and cyst fluid secretion.…”
Section: Introductionmentioning
confidence: 99%